Resonant Oscillation Language of a Futuristic Nano-Machine-Module: Eliminating Cancer Cells & Alzheimer Aβ Plaques - Ghosh, Subrata; Chatterjee, Somnath; Roy, Anirban; Ray, Kanad; Swarnakar, Snehasikta; Fujita, Daisuke; Bandyopadhyay, Anirban (Current Topics in Medicinal Chemistry, 2015)
Nano-machine-module is designed and synthesized as a futuristic drug (PCMS) for cancer and Alzheimers by doping 2 Nile Red molecules in the cavity of a 5th generation PAM AM dendrimer P, and attaching 32 molecular rotors M, 4 pH sensors S on its surface. Molecular rotors and sensors enable the dendritic box surface to target specific sites, minimizing termination of healthy cells, e.g. cancer cells, nuclei acids (DNA) & spirals of Abeta Amyloid are disintegrated. Combined Excitation Emission Spectroscopy (CEES) shows directed energy transfer along M↔C↔S, this energy transmission path is itself an oscillation, and we image live resonant oscillation of the PCMS and the target molecular system. PCMS engages into resonant oscillations with spiral molecular structures. PCMS is designed to sense microsatellite instability & spirals with resonance frequencies in the kHz range. PCM is toxic, but the toxicity disappears as S is added to derive PCMS. PCMS does not even affect the dynamic instability of microtubule, a basic operator of living cells.
Keywords: Molecular machine